Research Hotspot and Trend of Employee Creativity Based on Bibliometric Analysis - Shi, Yang; Zhang, Hong-yuan (Frontiers in Psychology, 2022)
Employee creativity is the foundation of organizational competitiveness, and it is also the important themes of creativity research. Based on the knowledge graph theory, this paper uses Citespace software to conduct bibliometric analysis of 1168 importance literature from Web of Science, and draws the co-citation and co-word clustering knowledge graph to explore research hotspots and trends of employee creativity. The research found that: First, the research on the connotation, dimensions and behavior of employee creativity is still in initial stage; Secondly，the research on the psychological, behavior and management factors that affect employee creativity, is the key content of common concern; Thirdly, it needs to comprehensively consider relevant factors from the combination of individuals, groups, and organizations about employee creativity research. On this basis, the paper proposes the main directions for future research.